Analisis Maslahah Mursalah Terhadap Pendapat Penghulu KUA Wonocolo Surabaya Tentang Nilai Mahar - Imam Nur Syamsuddin; Lailatul Widyawati; M. Ainur Rosidi; M. Dhiyaulhaq; Nova Riskiyana Setiyahani (AL-HUKAMA, 2019)
This paper is the result of research using field research methods to answer two questions, that is: how is the view of the head of KUA Wonocolo in carrying out the registration of marriages with low value for dowry and how is the analysis of the mas}lah}ah mursalah in fiqh and KHI on the view of the head of KUA Wonocolo in carrying out the registration of marriage which is nominally small. Data collection in this research was taken through interviews and documentation and then the data were analyzed using editing and organizing techniques. The opinion of the head of the KUA regarding the rejection of submissions for dowry with a small penalty occurred at KUA Wonocolo, Surabaya. According to the KUA Wonocolo, the dowry price can be an indicator of marriage readiness for the bride and groom. the opinion of the head of KUA regarding the dowry boundaries used by the head of KUA Wonocolo is based on the concepts of fiqh and KHI, which then the authors analyze with the concept of maslahah mursalah. The results of this research conclude that the aim of the head of KUA Wonocolo argues that he rejects the submission of dowry with a small penalty because, it is considered not to show the seriousness of the prospective husband to foster a household with his future wife and the opinion of the head of KUA Wonocolo is in accordance with the concept of mas}lah}ah mursalah.